Effect of subject motion and gantry rotation speed on image quality and dose delivery in CT‐guided radiotherapy. Issue 11 (15th August 2022) - Hrinivich, William T.; Chernavsky, Nicole E.; Morcos, Marc; Li, Taoran; Wu, Pengwei; Wong, John; Siewerdsen, Jeffrey H.
Abstract: Purpose: To investigate the effects of subject motion and gantry rotation speed on computed tomography (CT) image quality over a range of image acquisition speeds for fan‐beam (FB) and cone‐beam (CB) CT scanners, and quantify the geometric and dosimetric errors introduced by FB and CB sampling in the context of adaptive radiotherapy. Methods: Images of motion phantoms were acquired using four CT scanners with gantry rotation speeds of 0.5 s/rotation (denoted FB‐0.5), 1.9 s/rotation (FB‐1.9), 16.6 s/rotation (CB‐16.6), and 60.0 s/rotation (CB‐60.0). A phantom presenting various tissue densities undergoing motion with 4‐s period and ranging in amplitude from ±0.5 to ±10.0 mm was used to characterize motion artifacts (streaks), motion blur (edge‐spread function, ESF), and geometric inaccuracy (excursion of insert centroids and distortion of known shape). An anthropomorphic abdomen phantom undergoing ±2.5‐mm motion with 4‐s period was used to simulate an adaptive radiotherapy workflow, and relative geometric and dosimetric errors were compared between scanners. Results: At ±2.5‐mm motion, phantom measurements demonstrated mean ± SD ESF widths of 0.6 ± 0.0, 1.3 ± 0.4, 2.0 ± 1.1, and 2.9 ± 2.0 mm and geometric inaccuracy (excursion) of 2.7 ± 0.4, 4.1 ± 1.2, 2.6 ± 0.7, and 2.0 ± 0.5 mm for the FB‐0.5, FB‐1.9, CB‐16.6, and CB‐60.0 scanners, respectively. The results demonstrated nonmonotonic trends with scanner speed for FB and CB geometries. Geometric and dosimetric errors in adaptive radiotherapy plans were largest for the slowest (CB‐60.0) scanner and similar for the three faster systems (CB‐16.6, FB‐1.9, and FB‐0.5). Conclusions: Clinically standard CB‐60.0 demonstrates strong image quality degradation in the presence of subject motion, which is mitigated through faster CBCT or FBCT. Although motion blur is minimized for FB‐0.5 and FB‐1.9, such systems suffer from increased geometric distortion compared to CB‐16.6. Each system reflects tradeoffs in image artifacts and geometric inaccuracies that affect treatment delivery/dosimetric error and should be considered in the design of next‐generation CT‐guided radiotherapy systems.